PENGARUH CANDU TERHADAP ASPEK SOSIAL-BUDAYA DAN EKONOMI ETNIS TIONGHOA DI SAMBAS TAHUN 1909-1942 - Aris Munandar; Agus Sastrawan Noor; Andang Firmansyah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe research was titled "Opium Influence on socio-cultural aspects and ethnic Chinese economy in Sambas year 1909-1942". A common problem in this research is how opium influences the ethnic Chinese in Sambas in 1909-1942. The purpose of this research is to describe the opium influence of ethnic Chinese in Sambas in 1909-1942 in socio-cultural and economic aspects. The study uses historiography methods, namely Heutistics, source criticism, verification, and historiography. The approach used in the study was sociology, economics and politics. The results of this study showed that: (1) The opium trade was not separated from the coming of the Chinese to Sambas, the opening of the gold mine at Monterado and the trade route between West Borneo and Singapore; (2) Opium trade managed by the local government as well as during the Dutch East Indies, influenced the socio-cultural life of Chinese society, especially the disputes between Chinese society and Sultan Sambas and government Dutch Colonial Indies; (3) The government-run opium management system through the Regie system gives a large income to fill the colonial treasury. The Chinese smugglers also benefit from opium trading as there is no need to pay high taxes to the colonial government. However, the majority of Chinese consumers have a health loss that will also affect their economy.Keywords: Opium influence, ethnic Chinese, Sambas